Food waste prevention solutions in the annual reports of European companies - Cģtģlina Gorgan; Ionela-Corina Chersan; Voicu-Dan Dragomir; Mģdģlina Dumitru (Amfiteatru Economic Journal, 2022)
Food waste is a social, environmental, and economic challenge today. The European Union's Green Deal demands tackling this problem. Our research question is: "What are the solutions regarding food waste prevention across the companies' supply chain?" The mixed research method consisted of content and thematic analysis. We collected information from the reports published by European food companies that have joined the Green Deal and the Farm to Fork Strategy. The data were structured using a theoretical model in which we integrated ten essential stages of the food chain. The findings show that most of the information is reported for the manufacturing/production stage. Although transfer to landfill is unavoidable in supply chains, organizations make substantial efforts to reduce the proportion of food waste. The methods applied by food companies are inspired by European regulations regarding environmental protection. Our research identifies solutions brought about by the Green Deal on food waste prevention.
Keywords: M14; Q56; 330; food waste; regulations; reporting; Green Deal; European Union; food chain